Regulating Secondary Flow in Ultra‐Low Aspect Ratio Microchannels by Dimensional Confinement. Issue 4 (9th February 2018) - Shen, Shaofei; Kou, Lisha; Zhang, Xuan; Wang, Defu; Niu, Yanbing; Wang, Jinyi
Abstract: The ability to control the movement of fluids is significant in biological analysis, chemical synthesis, and medical diagnostics. Microfluidic technologies have achieved promising progresses in fluid manipulation by curvilinear channel geometries due to the presence of secondary flows. However, most of these devices are not designed in low aspect ratio microchannels because of the difficulty of weak Dean effect. Herein, we describe an inertial microfluidic system that allows deterministic regulation of secondary flows by geometric confinement in ultra‐low aspect ratio microchannels. On the introduction of a series of micro‐obstacles in semicircular microchannels, the resulting acceleration of secondary flow can be applied to remarkably potentiate many molecular interactions and reactions with a high mixing efficiency and speed under a wide range of flow capacity. The strategy to engineer secondary flow used in this work offers new insights pointing to low aspect ratio, ease‐to‐use, high‐throughput, and considerable flexibility for designing efficient microfluidic devices in diverse fluid manipulations. Abstract : An inertial microfluidic system relative to the deterministic regulation of secondary flows by geometric confinement is developed. The ultra‐low aspect ratio semicircular channel containing ordered micro‐obstacles permits easy‐to‐use (without complicated fabrication of multilayered structures), high and broad flow capacity (≈2–20 mL min −1, without parallel device design), and efficient (almost 100% biochemical molecule mixing) operation in a smaller channel path.